A Model of Legal Culture for Prevention of Money Politics Through Social Media Strategies for Facing Simultaneous Elections in 2024 Gorontalo Province - Jupri; Arhjayati Rahim; Rusmulyadi, Rusmulyadi; Vicky Ibrahim; Umar P (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This research aims to examine and explore the construction of a legal culture model for monitoring social movements to prevent money politics through social media and describe forms of legal protection for this movement. From the experience of previous simultaneous elections and local elections, various problems remain, one of which is money politics. Money politics is considered a differentiation mechanism for contestants to provide more value than other contestants in order to pursue personal votes. The factors vary, from weak religious culture, strong kinship culture, and paternalistic culture. This research provides a prevention model by utilizing social media such as Facebook, Twitter, WhatsApp and Instagram as a tool for social movements to prevent the practice of money politics. The type of research used is empirical research, namely research with field data as the main data source. The results of this research show that there are two models of cultural construction of legal supervision of social movements to prevent money politics through social media, namely the formation of anti-money politics citizen forums based on social media and creating anti-money politics fosters on social media. Meanwhile, the form of protection for this movement is to strengthen regulations and legal protection for whistleblowers and pay attention to Law Number 31 of 2014 concerning the protection of witnesses and victims. In the future, social media can be used as a means for more massive social movements to voice ideas, opinions and views in monitoring deviant behavior from political contestants and there needs to be special arrangements for the protection of these social movements.